ANALISIS DAMPAK PENGGUNAAN GENERATIVE AI (CHATGPT) TERHADAP INTEGRITAS AKADEMIK MAHASISWA DI PENDIDIKAN TINGGI - Parhusip, Jadiaman; Agustin, Olga Noviola; Ferdinand, Bryan Desmonda; Saputra, Rendy; Rangin, Adriel Eleazar (STMIK BINA PATRIA, 2025)
The rapid adoption of Generative AI, such as ChatGPT, in higher education has sparked significant debate regarding its impact on academic integrity. This research aims to analyze the ethical and social impacts of using Generative AI on student academic integrity. This study uses the Systematic Literature Review (SLR) method. Literature was searched from databases like Google Scholar and Scopus published between 2022 and 2025. After applying inclusion and exclusion criteria, 10 relevant articles were selected for synthesis. The results identify several key themes: (1) Increased risk of novel forms of plagiarism and academic dishonesty, (2) a potential decline in critical thinking and original writing skills, (3) the urgent need for new institutional policies and ethical guidelines, and (4) the dual role of AI as both a learning aid and a sophisticated cheating tool. This study concludes that while Generative AI offers potential as a learning aid, its unregulated use poses a significant threat to traditional academic integrity.